Military Backgrounds in Shaping Earnings Management: Insights from the Board of Commissioners and Directors - Irianto, Agung; Kurniawati, Estetika Mutiaranisa (Universitas Ahmad Dahlan, 2025)
This study aims to determine the effect of the military background of the board of commissioners and directors on earnings management practices in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The research uses a quantitative approach, utilizing secondary data obtained from annual reports published on the Indonesia Stock Exchange and on the official websites of each company. Using panel data regression analysis, the findings indicate that companies with a board of commissioners and a military background negatively affect earnings management. Meanwhile, directors with military experience do not affect earnings management. This study utilizes the military background variable of the company's top management, which is still rarely used in earnings management research, particularly in Indonesia. This research contributes as a guideline for company stakeholders, especially investors, regarding the potential risks and benefits associated with earnings management in companies with a board of commissioners and directors with military backgrounds.